Learner Voice: How Learner-Centered Programming Affects Teacher-Centered Instruction - Patsy Medina (Adult Education Research Conference, 2002)
Similar to other research in adult literacy education, my study confirms that adult literacy education primarily focuses on building discrete skills. However, when one examines the programming decisions that administrators make, there is a difference in how and what students learn in the classroom.